Effect of melatonin on formation of 8-oxo-2’-deoxyguanosine under fenton reaction conditions - N. V. Marmiy; T. S. Nevredimova; D. S. Esipov (Тонкие химические технологии)
In this paper we studied the effect of melatonin at three concentrations on the formation of 8-oxo-2'-dioxyguanosine (8-oxo-dG) under the conditions of the Fenton reaction. Reproducible kinetic curve of 8-oxo-dG accumulation in this reaction was obtained by the method of reversedphase high performance liquid chromatography with amperometric detection. When adding melatonin in all three concentrations studied, there was a noticeable change in the shape of the kinetic curve with a significant decrease in the amount of detected 8-oxo-dG in most of its control points. This suggests the melatonin inhibition of 8-oxo-dG formation in the reaction and confirms the hypothesis of a direct, non-hormonal, antioxidant effect of melatonin. However, the dependence of the inhibitory effect of melatonin on its concentration is not a straight line. The higher of the studied concentrations of melatonin (60 mg/ml) gave the least pronounced effect.